Curdlan sulphate modulates protein synthesis and enhances NF-κB and C/EBP binding activity in HepG2 cells - A. Guzdek; H. Rokita (Mediators of Inflammation)
In human hepatoma HepG2 cell line curdlan sulphate enhances basal and interleukin-6-stimulated fibrinogen and antichymotrypsin (ACT) synthesis, slightly increases basal ceruloplasmin production and exerts only minor effects on alpha-1-proteinase inhibitor and transferrin. Curdlan sulphate may, at least in part, affect protein synthesis at a pretranslational level, as the expression of ACT mRNA was found to be increased, whereas intracellular enzyme, manganese superoxide dismutase mRNA level was decreased in the cell culture treated with curdlan sulphate. Gel mobility shift analysis revealed that curdlan sulphate increases the DNA binding activity of NF-κB and C/EBP, suggesting that these transcription factors may participate in the regulatory effects of curdlan sulphate in HepG2 cells.